1981
DOI: 10.1007/bf01820175
|View full text |Cite
|
Sign up to set email alerts
|

The Okahandja Lineament and its significance for Damaran tectonics in Namibia

Abstract: The Okahandja Lineament is considered to represent the southern margin of a magmatie arc produced by the northerly subduction of the Damran Ocean between 750 and 520 Ma ago. Sediments of the Orogen and granitoid intrusives produced by subduetion and crustal melting, underwent shear deformation between 675 and 575 Ma in a low angle zone of sinistral sense shear.The Okahandja Lineament represents a zone of differential movement between the Central and Southern Zones of the Orogen during this simple shear deforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…A prolonged intrusive activity in the Central Zone core of the Damara Belt, approximately between 580 Ma (Allsopp et al, 1983, unconstrained U-Pb zircon age) and 470-460 Ma Veevers, 2007), was synchronous with intense polyphase deformation (Barnes and Sawyer, 1980;Downing and Coward, 1981;Kröner, 1982;Kasch, 1983;Nex, 1997;Poli, 1997) and high-T low-P metamorphism (Puhan, 1983;Masberg et al, 1992;Nex et al, 2001;, with increasing temperature along strike to the SW (Goscombe et al, 2004). The Pan-African plutonism, exposed over one third of the entire area of the inland branch, resulted in more than 300 syn-and post-tectonic intrusions and thousands of granitic and pegmatitic dykes (Miller, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…A prolonged intrusive activity in the Central Zone core of the Damara Belt, approximately between 580 Ma (Allsopp et al, 1983, unconstrained U-Pb zircon age) and 470-460 Ma Veevers, 2007), was synchronous with intense polyphase deformation (Barnes and Sawyer, 1980;Downing and Coward, 1981;Kröner, 1982;Kasch, 1983;Nex, 1997;Poli, 1997) and high-T low-P metamorphism (Puhan, 1983;Masberg et al, 1992;Nex et al, 2001;, with increasing temperature along strike to the SW (Goscombe et al, 2004). The Pan-African plutonism, exposed over one third of the entire area of the inland branch, resulted in more than 300 syn-and post-tectonic intrusions and thousands of granitic and pegmatitic dykes (Miller, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…The effects of differential shear on fold hinges within the more internal portions of orogenic belts were also discussed by Downing & Coward (1981) in the Damaran belt of Namibia. Following the proposals made by Elliott (1976), Coward & Potts (1983) demonstrated that intense shear strains (71) may develop at the frontal tips to thrusts and shear zones, where layer-parallel shortening will lead to folding at a high angle to transport ( Fig.…”
mentioning
confidence: 98%
“…Northeast-directed subduction of this ocean floor beneath the leading edge of the Congo Craton, referred to as the Okahandja Lineament (Miller 1979;Downing and Coward 1981; Fig. 2), resulted in uplift and erosion of the frontal region of the Congo Craton and the Central Zone of the Damara Belt (Fig.…”
Section: Continental Rupturementioning
confidence: 99%